Is Carotid Body Physiological O2 Sensitivity Determined by a Unique Mitochondrial Phenotype? - Holmes, Andrew P.; Ray, Clare J.; Coney, Andrew M.; Kumar, Prem (Frontiers in Physiology, 2018)
The mammalian carotid body (CB) is the primary arterial chemoreceptor that responds to acute hypoxia, initiating systemic protective reflex responses that act to maintain O2 delivery to the brain and vital organs. The CB is unique in that it is stimulated at O2 levels above those that begin to impact on the metabolism of most other cell types. Whilst a large proportion of the CB chemotransduction cascade is well defined, the identity of the O2 sensor remains highly controversial. This short review evaluates whether the mitochondria can adequately function as acute O2 sensors in the CB. We consider the similarities between mitochondrial poisons and hypoxic stimuli in their ability to activate the CB chemotransduction cascade and initiate rapid cardiorespiratory reflexes. We evaluate whether the mitochondria are required for the CB to respond to hypoxia. We also discuss if the CB mitochondria are different to those located in other non-O2 sensitive cells, and what might cause them to have an unusually low O2 binding affinity. In particular we look at the potential roles of competitive inhibitors of mitochondrial complex IV such as nitric oxide in establishing mitochondrial and CB O2-sensitivity. Finally, we discuss novel signaling mechanisms proposed to take place within and downstream of mitochondria that link mitochondrial metabolism with cellular depolarization.